USING THE COMBINATION OF THE 3D GRAVITY INVERSION METHOD WITH THE DIRECTIONAL ANALYTIC SIGNAL DERIVATIVES AND THE CURVATURE GRAVITY GRADIENT TENSOR METHOD TO DETERMINE STRUCTURE OF THE PRE-CENOZOIC BASEMENT ON SOUTHEAST CONTINENTAL SHELF OF VIETNAM - Dung, Nguyen Kim; Thanh, Do Duc; Vuong, Hoang Van; Thu, Duong Thi Hoai (Vietnam Journal of Marine Science and Technology, 2019)
In this paper, we present some new results of the Pre-Cenozoic basement structure on the Southeast continental shelf of Vietnam based on the combination of some modern methods to analyse and interpret gravity data. They are the 3D gravity inversion method, the directional analytic signal derivatives and the curvature gravity gradient tensor. The results obtained include the density distribution, the fault system and the main structural blocks inside of the Pre-Cenozoic basement on Southeast continental shelf of Vietnam. The initial results about density distribution show that it relatively clearly reflects the shape of basins in the area: The contours that have value σ =2.7 g/cm3 and value σ = 2.76 g/cm3 are near the edges of the Cuu Long basin and the Nam Con Son basin, respectively. The density value reaches the maximum at the center of basins. For the Cuu Long basin, the maximum value is σmax= 2.76 g/cm3 and the Nam Con Son has maximum value σmax= 3.0 g/cm3. Many faults that appear in the study area have the existence depth in the wide range from 6 km to 30 km, even above 30 km and the faults that have the existence depth from 8 to 10 km are in the majority. In particular, the boundary of anomalous sources existing in the Pre-Cenozoic basement is shown by the better resolution, at which more edge points are identified than the maximum horizontal gradient amplitude method that is widely used. The results also show that the combination of individual results complements each other and creats the sufficient and clearer picture inside of the Pre-Cenozoic basement.